Distributed Image Compression and Transmission Scheme in Wireless Multimedia Sensor Networks - Enyan Sun; Xuanjing Shen; Haipeng Chen; Chuanyun Wang (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Wireless multimedia sensor networks will have a variety of applications. Meanwhile, WMSNs produce a large amount of image data. JPEG2000 is the popular image compression standard and have some advantages. However, JPEG2000 is also high complexity and cannot be realized in an individual senor node which is limited in memory capacity, computation power and energy. Distributed image compression and transmission scheme is proposed to overcome the problem of scarce resources of the individual sensor node and uneven energy consumption. Simulation experiments show that DICT can more evenly consume the energy of senor nodes in WMSNs and prolong the network lifetime comparable to centralized image compression and transmission scheme. DOI : http://dx.doi.org/10.11591/telkomnika.v12i1.3739